Sex Traffickers: Friend or foe? - Hamid, Haezreena (Anti-Trafficking Review, 2022)
This article addresses the knowledge gap surrounding human traffickers in Malaysia. Based on qualitative interviews with women identified as victims of trafficking, it explores the women’s perception of their traffickers and their migration experience. The article asserts that the term ‘trafficker’ is complex and misunderstood by scholars, states, and state officials; and that trafficked persons may not necessarily detest their traffickers or even regard them as having caused them harm. Instead, traffickers are sometimes considered ‘helpers’ or people who provide work opportunities and a prospect of a better life. However, this form of relationship is considered exploitative by Malaysian legislation.